The effect of women executives on bank risk: evidence from Indonesia - Oktafiani, Esther Putri; Kurnianti, Destria (Ifma Publishing, 2023)
This study examined the effect of women executives on bank risk in banks listed on the Indonesia Stock Exchange between 2017 and 2021. Women executives served as the independent variable. The dependent variable was bank risk, which is a proxy for non-performing loans and capital adequacy ratio. The financial statements of banks listed on the Indonesia Stock Exchange from 2017-2021 were used as the data source. This study used the purposive sampling method to select the sample. Panel data with the fixed effect model approach was applied in this study as the research model. According to the findings, women CEOs do not significantly affect non-performing loans and capital adequacy ratios. This is because there are no regulations requiring gender equality on company management boards, particularly in Indonesian banks, as well as challenges from social society toward women.